Potential Molecular Mechanism of TNF Superfamily-Related Genes in Glioblastoma Multiforme Based on Transcriptome and Epigenome - Xie, Hui; Yuan, Ce; Li, Jin-jiang; Li, Zhao-yang; Lu, Wei-cheng (Frontiers in Neurology, 2021)
Objective: This study aimed to investigate the molecular mechanism of tumor necrosis factor (TNF) superfamily-related genes and potential therapeutic drugs for glioblastoma multiforme (GBM) patients based on transcriptome and epigenome. Methods: Gene expression data, corresponding clinical data, and methylation data of GBM samples and normal samples in the TCGA-GBM and GTEx datasets were downloaded. The TNF-related genes were obtained, respectively, from two groups in the TCGA dataset. Then, the TNF-related differentially expressed genes (DEGs) were investigated between two groups, followed by enrichment analysis. Moreover, TNF superfamily-related gene expression and upstream methylation regulation were investigated to explore candidate genes and the prognostic model. Finally, the protein expression level of candidate genes was performed, followed by drug prediction analysis. Results: A total of 41 DEGs including 4 ligands, 18 receptors, and 19 downstream signaling molecules were revealed between two groups. These DEGs were mainly enriched in pathways like TNF signaling and functions like response to TNF. A total of 5 methylation site-regulated prognosis-related genes including TNF Receptor Superfamily Member (TNFRSF) 12A, TNFRSF11B, and CD40 were explored. The prognosis model constructed by 5 genes showed a well-prediction effect on the current dataset and verification dataset. Finally, drug prediction analysis showed that zoledronic acid (ZA)-TNFRSF11B was the unique drug–gene relation in both two databases. Conclusion: Methylation-driven gene TNFRSF12A might participate in the development of GBM via response to the TNF biological process and TNF signaling pathway and significantly associated with prognosis. ZA that targets TNFRSF11B expression might be a potential effective drug for clinical treatment of GBM.